A Critical Analysis of the Literature Regarding Cyber-Violence and Social Media Awareness in the Context of Teacher Education - Laghari, Hamid (Journal of Advanced Research in Journalism & Mass Communication, 2022)
The extended plans are supported by multilateral and new literary literacy teachings, which place a greater emphasis on the technology of developing technologies in educational settings. However, there is no controversy within the education field about the ethical repercussions that may result from the use of social media in the teacher. The fact that the area on the internet is likely to be hazardous is something that should be of particular concern. In particular, the social networking tool known as Twitter, which is utilized and encouraged by many teachers to work on professional learning networks, is rife with inappropriate conduct and racist abuse. The present paper will explain the ethical consequences for teachers who develop an academic to develop important social media awareness activities by conducting a review of existing research on the use of social media in teaching and taking a multi-disciplinary approach to issues relating to cyber-violence. This will be done through the medium of writing. Employ Twitter as a useful tool. Want to put these methods to practice and create more of them.